A palliative accelerated irradiation regimen for advanced non-small-cell lung cancer vs. conventionally fractionated 60 GY: results of a randomized equivalence study - Nestle, Ursula; Nieder, C.; Walter, K.; Abel, Ulrich; Ukena, D.; Sybrecht, G. W.; Schnabel, K. (International journal of radiation oncology, biology, physics, 2000)
PURPOSE: Radiation oncologists are often faced with patients with advanced non-small-cell lung cancer (NSCLC), who are not suitable candidates for state-of-the-art radical treatment, but who also are not judged to have a very short life expectancy. Some physicians treat these patients palliatively, whereas others advocate more intensive treatment. To find out if there is a substantial difference in outcome between these approaches, we performed a randomized prospective study. METHODS AND MATERIALS: Between 1994 and 1998, 152 eligible patients with advanced NSCLC Stage III (n = 121) or minimal Stage IV (n = 31) were randomized to receive conventionally fractionated (cf; A: 60 Gy, 6 weeks, n = 79) or short-term treatment (PAIR; B: 32 Gy, 2 Gy b.i.d.; n = 73) of tumor and mediastinum. RESULTS: One-year survival rate for all patients was 37% with no significant difference between the two treatment arms (A: 36%; B: 38%; p = 0.76). As far as can be judged from limited data available, palliation was adequate and similar for the two treatment arms. Apart from expected differences in the time course of esophagitis, acute side effects were moderate and equally distributed. No severe late effects were observed. CONCLUSIONS: In the present randomized trial, survival and available data on palliation were not different after cf to 60 Gy compared to the palliative PAIR regimen. Therefore, for patients who are not suitable for radical treatment approaches, the prescription of a palliative short-term irradiation appears preferable compared to cf over several weeks.